Health and Educational Inequalities among the Third Gender Community in Lahore, Pakistan - Ayesha Humayun; Muhammad Hassan; Hira Ashfaq; Zulqarnain Haider; Nauman Naeem; Mubashar Munir (Journal of University College of Medicine and Dentistry)
Objective: The third gender community, commonly referred to as the ‘hijra’ community and including transgender, intersex, and eunuch individuals, faces widespread societal discrimination, leading to marginalization and reduced opportunities for social and economic participation. This study aims to explore the educational and healthcare challenges faced by this community, as perceived by its members, to gain deeper insight into the complexities of their lived experiences.